Integrated Morphometric and Pedological Approach for Mapping Groundwater Availability Potential of Urban Watersheds: Case Study of the Former Municipality of Ratoma (Guinea) - Tokpo Ninamou; Manou Bernadin Elegbede; Mory Kourouma; Tchantipe NTcha; Sine Diakite (European Scientific Journal, ESJ, 2026)
To address water supply challenges in urban zones, this study proposes an integrated approach to characterize the water availability potential of the watersheds in the municipality of Ratoma in Guinea. This work combines remote sensing, Geographic Information Systems, pedology, and multivariate statistical analysis. Based on the DTM, 38 watersheds were characterized based on 23 morphometric parameters. Principal Component Analysis explained 72,92% of the total variance across three axes: size and drainage (39,86%), relief energy (18,79%), and the shape and compactness axis (14,28%). Hierarchical ascending classification identified two functional groups: small basins (0,16-1,67 km²) with rapid hydrological response, and larger basins (1,76-7 km²) with slower dynamics. Simultaneously, pedological analysis identified nine soil units, dominated by skeletal formations (75%) with rapid drainage. Soil granulometric analysis revealed textural variability that can influence infiltration. Coarse soils have high infiltration capacity but low water retention, while fine soils display temporary hydromorphism. Combining the results allowed for the spatial identification of areas with high water potential (hydromorphic soils) and transit areas (skeletal soils). Nevertheless, the hydrological responses remain hypothetical and do not allow for the establishment of predictive capacities for flow rates or recharge. Therefore, hydrogeological investigations remain necessary to refine the methodological approach used in order to produce a decision-making tool for the sustainable management and planning of water resources, facilitating the choice of drilling sites.